Study on Echo Characteristics of Narrow Pulse Laser Fuze on Targets in Cloud - Li Lekun, Li Yuan, Gao Chong, Tu Jianping (Editorial Office of Aero Weaponry, 2021)
Due to the working characteristics of laser fuze, it is easy to be interfered by cloud, thus causing false alarm. Therefore, it is necessary to improve the ability of laser fuze to resist the cloud interference. Monte Carlo method is used to analyze the echo characteristics of targets in cloud under different pulse width laser, and carry out relevant tests to verify. The results of mathematical simulation and experiment show that the narrow pulse laser fuze can effectively suppress the cloud echo, improve the fuze’s ability to identify targets in the cloud and anti-cloud interference ability, and reduce false alarm.